PENGEMBANGAN BAHAN AJAR FLIPBOOK BERBANTUAN APLIKASI ANYFLIP MATERI PERUBAHAN ENERGI DI SEKITAR KITA - Rizkika, Nabila; Yuli Mulyawati; Ade Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Nabila Rizkika. 037120131. This research aims to determine the development of the Flipbook assisted by the Anyflip Application on the Material of Energy Changes Around Us which was created for class IV students at SDS Islam Nurul Iman and to determine the feasibility of the Flipbook assisted by the Anyflip Application for the learning process at school. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. Validation tests were carried out on media experts, language experts and material experts to develop and perfect the Flipbook assisted by the Anyflip Application for students and questionnaires, pre-test and post-test questions were distributed to students as well as to determine the suitability of the Flipbook assisted by the Anyflip Application in learning. The results of the validation test showed that media experts with a percentage of 98% met very feasible criteria, language experts with a percentage of 98% met very feasible criteria, and material experts with a percentage of 80% met very feasible criteria. These results show that Flipbook is very suitable to be developed for students and is very suitable to be used as teaching material in learning